PENANGANAN MENINGKATKAN BERAT BADAN PADA BAYI BERAT LAHIR EKSRIM RENDAH (BBLER) DI NICU RSUD TEMANGGUNG - Ratriyana, Dani Okta; Mustajab, Abdullah Azam; Azuma, Anindita Paramastuti; Indriani, Farihah (Jurnal Ilmiah Kesehatan, 2023)
The purpose of this study was to analyze the effect of treatment to increase body weight in ELBW in the NICU of Temanggung Hospital. Preterm babies can be classified based on weight and age. Based on body weight, one of them is an extreme low birth weight (ELBW) baby with a weight < 1000 grams and based on gestational age one is an extreme premature baby with a gestational age < 27 weeks. This situation can become a health problem that has an impact on his life such as disability, decreased learning ability and problems with vision and hearing. The quantitative research method used pre-experimental one group pre-test and post-test design. Sample using total sampling with the number of respondents 6 babies. The research data was carried out by the Shapiro Wilk test and the Wilcoxon test. The results of the study explained that after being given interventions to increase body weight in ELBW for 28 days, ELBW weight increased with an average weight gain of 461.17 grams and obtained a p-value of 0.028 <0.05, which means that there is a significant effect of treatment on increasing baby weight. Conducted on ELBW weight in the NICU of the Temanggung Hospital. The conclusion of interventions for handling increased weight in ELBW by providing several treatments such as ASI, PASI and fortification, using the kangaroo method, massage therapy, music therapy and orotherapy can increase body weight in ELBW who are treated in the NICU Temanggung Hospital.